Community Empowerment Based on Local Materials - Setiawati, Setiawati; Aini, Wirdatul'; Pridayati, Lucy (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
Community empowerment through local resource-based training is a strategic effort to enhance skills and economic independence, particularly in rural areas. This training program aims to utilize locally available resources, such as natural materials and agricultural products, to create high-value-added products. By involving the community in the learning and production process, the training can improve individual capacities and strengthen the local economy. Additionally, the use of local materials promotes environmental sustainability by reducing reliance on imported or environmentally harmful materials. The program’s outcomes are expected to generate new job opportunities, increase community income, and raise awareness of the importance of optimizing local resources.Key Word : Community empowerment  , local resource , training is a strategic